Sponge microbiome stability during environmental acquisition of highly specific photosymbionts. (5th August 2020) - Britstein, Maya; Cerrano, Carlo; Burgsdorf, Ilia; Zoccarato, Luca; Kenny, Nathan J.; Riesgo, Ana; Lalzar, Maya; Steindler, Laura
Summary: In this study, we used in situ transplantations to provide the first evidence of horizontal acquisition of cyanobacterial symbionts by a marine sponge. The acquisition of the symbionts by the host sponge Petrosia ficiformis, which was observed in distinct visible patches, appeared several months after transplantation and at different times on different sponge specimens. We further used 16S rRNA gene amplicon sequencing of genomic DNA (gDNA) and complementary DNA (cDNA) and metatranscriptomics to investigate how the acquisition of the symbiotic cyanobacterium Candidatus Synechococcus feldmannii perturbed the diverse microbiota associated with the host P . ficiformis . To our surprise, the microbiota remained relatively stable during cyanobacterial symbiont acquisition at both structural (gDNA content) and activity (cDNA expression) levels. At the transcriptomic level, photosynthesis was the primary function gained following the acquisition of cyanobacteria. Genes involved in carotene production and oxidative stress tolerance were among those highly expressed by Ca . S. feldmannii, suggesting that this symbiont may protect itself and its host from damaging light radiation.